THE PHASES OF INDUSTRIAL DEVELOPMENT IN SABAH - Firdausi Suffian (International Journal of Accounting, Finance and Business, 2022)
This paper is a preliminary assessment of the industrial development in Sabah. It is widely known industrial development is the primary key to modernise an economy and structural change. Transition of structural change requires the state to configure coherent industrial policy to ensure industrial development can take place. Throughout the history of Sabah industrial development, the state has continuously attempted to industrialise the state but transition to pursue structural change is limited. This limitation is due to the inefficacy of planning and implementation of industrial policy which is influenced by political dynamic of the state and federal-state relations. This paper examines phases of industrial development and political dynamics of the state. Policy priority defines by elite policymaker and asymmetrical power relations between federal and state government can likely hinder a desired trajectory of industrial policy outcome.